Optimization of low-grade CGO transport properties for SOFC applications - Gomes, Eduarda (2022)
Grain boundaries are frequently responsible for a poor performance of gadolinium-doped ceria-based electrolytes, due to a low ionic conductivity, orders of magnitude smaller than the bulk conductivity. Silica, the dominant impurity in many low-grade ceramics, namely, in ceria-based materials, has a detrimental effect on grain boundaries conductivity. Several previous works had explored the silica-scavenging effect. In the present work, we exploit an alternative approach using the addition of 5% (w/w) of Y2O3, as silica scavenging agent, and sintering by hot pressing at low temperature to minimize bulk dissolution of yttrium in the CGO lattice. Gadolinium-doped ceria-based powders were co-fired with additions of 1% (w/w) of silica, and silica and yttrium oxide to test the silica scavenging role of yttrium. The samples were prepared by hot press at low temperature (1000ºC) and were characterized by impedance spectroscopy as a function of temperature in air, in order to de-convolute different microstructural contributions to the overall electrical behaviour. Combined information obtained from structural, microstructural, and electrical characterization allowed one to study the impact of new phases on the resulting ceria-based solid electrolytes.